Effects of hydropeaking on the attached eggs of a rheophilic cyprinid species - Bartoň, Daniel (Jihočeská univerzita, 2023)
Ability of eggs of asp (Leuciscus aspius) to survive an increased water velocity was tested in experimental condition as well as in situ. Hydropeaking occurs on the study site and can cause detachment of most spawned eggs.
Effects of hydropeaking on the attached eggs of a rheophilic cyprinid species
Keywords: fish reproduction; Leuciscus aspius; wildlife conservation; river ecology; habitat alternation